Total Phenolic, Flavonoid, Tomatine, and Tomatidine Contents and Antioxidant and Antimicrobial Activities of Extracts of Tomato Plant - Norma Patricia Silva-Beltrán; Saul Ruiz-Cruz; Luis Alberto Cira-Chávez; María Isabel Estrada-Alvarado; José de Jesús Ornelas-Paz; Marco Antonio López-Mata; Carmen Lizette Del-Toro-Sánchez; J. Fernando Ayala-Zavala; Enrique Márquez-Ríos (International Journal of Analytical Chemistry)
The purpose of this study was to evaluate the antioxidant and antimicrobial properties of extracts of different fractions of two tomato plant cultivars. The stems, roots, leaves, and whole-plant fractions were evaluated. Tomatine and tomatidine were identified by HPLC-DAD. The leaf extracts from the two varieties showed the highest flavonoids, chlorophyll, carotenoids, and total phenolics contents and the highest antioxidant activity determined by DPPH, ABTS, and ORAC. A positive correlation was observed between the antioxidant capacities of the extracts and the total phenolic, flavonoid, and chlorophyll contents. The Pitenza variety extracts inhibited the growth of pathogens such as E. coli O157:H7, Salmonella Typhimurium, Staphylococcus aureus, and Listeria ivanovii, yielding inhibition halos of 8.0 to 12.9 mm in diameter and MIC values of 12.5 to 3.125 mg/mL. These results suggest that tomato plant shows well potential as sources of various bioactive compounds, antioxidants, and antimicrobials.